Co-Constructing A Praxis for Critical Pedagogies of Care in Postdigital Tertiary Education - Brown, Cheryl; Tolbert, Sara (Proceedings of the International Conference on Networked Learning, 2024)
Like others in 2020, we found ourselves grappling with the sudden shift to fully online teaching and learning during COVID19 and the very pronounced negative impact of the sudden shift on students and faculty alike (Authors and colleague, 2022). In Aotearoa New Zealand emerging research revealed how tertiary students’ experiences of online learning during COVID19 were characterized by stress and anxiety, compounded by difficulties in communication between students, instructors, and support staff as well as by loss of income and limited access to campus resources. These challenges were even more pronounced among already marginalized students, such as Māori tertiary students. Simultaneously, messaging from ‘managers’ in our neoliberal university context was increasingly about ‘pastoral care for students,’ a message which we struggled to make sense of given the nature of the very real socio-political challenges our students faced. Confronting the uncertainties of COVID and related future crises we set out to explore how we could better plan for and accommodate increased flexibility and adaptability in instruction that is responsive to both students and current social contexts–given that, a) throughout the COVID19 pandemic, students and instructors were frequently absent due to illness even when on campus instruction resumed in New Zealand, and b) periodic lockdowns were part of the COVID19 management strategy in NZ, which meant sudden shifts to fully online instruction throughout the 2020-2022 academic years. Our premise was that the crisis required thoughtful deliberation on how we, as tertiary educators, might collectively address such a significant global challenge in our local context. We (authors) applied for and were awarded a 2-year leadership in teaching fellowship, a new fellowship program that aimed to support faculty innovation in teaching. The fellowship allowed us time to slow down and interrogate our approach to postdigital education during the period of Covid19, as well as beyond it. We sought out to ask critical questions of ourselves, such as those related to the form/manner in which we were using digital tools, what was meant by ‘pastoral care’ for students and what that should/could look like in postdigital pandemic times, questioning the discourses and aspirations around a post-pandemic ‘return to normal’.